In situ observation on two ‘elusive’ rhodaliid siphonophores (Cnidaria; Hydrozoa; Siphonophora) from the Red Sea, including a potential new species within the genus Archangelopsis - Angulo-Preckler, Carlos; Steckbauer, Alexandra; Lim, Kah Kheng; Hissmann, Karen; Pieribone, Vincent; Qurban, Mohammad; Duarte, Carlos M. (Frontiers in Marine Science, 2024)
Rhodaliids, a specific family of siphonophores inhabiting the benthic zone, have remained enigmatic due to their rarity and elusive nature. These unique organisms, primarily found in open ocean habitats, exhibit distinctive features and are characterized by complex structures. During the Red Sea Decade Expedition, two rhodaliid specimens were collected at the sea bed at water depths of 438 and 495 meters. Regardless of challenges in specimen preservation, detailed morphological analysis revealed unique characteristics. Genetic analysis, employing the 16S rRNA marker, revealed one specimen closely related to Thermopalia taraxaca, while the taxonomic traits of this specimen suggested the identification of Archangelopsis jagoa. While most of the morphological features of the second specimen were also very similar to A. jagoa, some differences in coloration suggest the discovery of either an unusual colour variant or a potential new species within this genus. Notably, this study reports the first sequencing of A. jagoa. This species demonstrated a capacity to thrive in low-oxygen environments, challenging conventional assumptions about their habitat requirements. Despite difficulties in specimen handling and genetic analysis limitations due to a lack of comprehensive data, this research sheds light on the elusive world of benthic rhodaliids.